Adolescents’ and Young People’S Experiences of Social Relationships and Health Concerns During Covid-19 - Vergara-Del Solar, A (Taylor and Francis Ltd., 2023)
Purpose: To illuminate the meaning of social relationships and health concerns as experienced by adolescents and young people during the COVID-19 pandemic. Methods: A longitudinal qualitative study was conducted. Data reported from 172 adolescents and young people aged 12–24 years in five countries; Chile, South Africa, Sweden, the United Kingdom and the United States collected from May 2020 to June 2021 were analysed via thematic analysis. Results: Adolescents and young peoples’ experiences of social relationships and health concerns were described in seven themes: Family proximity, conflicts and frustration; difficulties and challenges related to limited living space; peer relations and maintaining friendship in times of social distancing; the importance of school as a place for interaction; vulnerability, emotional distress and uncertainty about the future; health concerns and sense of caring for others; and worries and concerns related to financial hardship. These reports show that the changes to everyday life that were introduced by public responses to the pandemic generated feelings of loneliness, vulnerability, and emotional distress, as well as increased sense of togetherness with family. Conclusions: The everyday lives of adolescents and young people were restricted and affected more by the consequences of the pandemic than by the COVID-19 virus. These experiences had various impacts on well-being and mental health, where some individuals felt more exposed and vulnerable to emotional distress and loneliness than others. Family and peer relationships could be protective and support a sense of togetherness and belonging. Hence, social relationships are important to provide emotional support. Support for adolescents and young people should be tailored accordingly around social and emotional concerns, to encourage health and well-being. © 2023 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.